Contestação social e ressentimento de classe no Brasil: uma análise sociológica do bolsonarismo e da mobilização do protesto conservador em uma rede social digital (2016-2019) - Agnoletto, Bharbara Alves (2022)
This work aimed to carry out a sociological analysis of the social contestation and class resentment present in the mobilizations and protests of conservatives and bolsonaristas on the social network Twitter, between 2016 and 2019. With their advanced search tool, from pre-defined categories. A total of 1615 publications were selected, which were stored and classified using the RQDA package for qualitative data analysis of the R programming language and the RStudio software. The reproduction of a certain class habitus that perpetuates forms of aporophobia in Brazilian society was perceived, as inciting a class conflict catalyzed by the small upward social mobility in PT governments and resulting in distinct types of mobilization of the middle classes. In addition, the posts on the social network reveal a conservative worldview that is susceptible to manipulation and political-ideological polarization through content with a strong emotional appeal. In the same way, Jair Bolsonaro is treated in the posts as a charismatic leader who mobilizes through the social network in question, a certain set of moral feelings, of which resentment is notable, through a strategy of propaganda and political agitation of a character “neo-fascist”, which represents, in the current sociopolitical conflict of the country, the emergence of a political position situated on the extreme right of the political-ideological spectrum. Finally, a form of justification for inequality was perceived in the analyzed material, capable of being configured in a conservative sociodicy that provides the metric of values for comparisons that give rise to the fear of relative deprivation of class privileges.